Medicalization of global health 4: the universal health coverage campaign and the medicalization of global health - Jocalyn Clark (Global Health Action, 2014)
Universal health coverage (UHC) has emerged as the leading and recommended overarching health goal on the post-2015 development agenda, and is promoted with fervour. UHC has the backing of major medical and health institutions, and is designed to provide patients with universal access to needed health services without financial hardship, but is also projected to have ‘a transformative effect on poverty, hunger, and disease’. Multiple reports and resolutions support UHC and few offer critical analyses; but among these are concerns with imprecise definitions and the ability to implement UHC at the country level. A medicalization lens enriches these early critiques and identifies concerns that the UHC campaign contributes to the medicalization of global health. UHC conflates health with health care, thus assigning undue importance to (biomedical) health services and downgrading the social and structural determinants of health. There is poor evidence that UHC or health care alone improves population health outcomes, and in fact health care may worsen inequities. UHC is reductionistic because it focuses on preventative and curative actions delivered at the individual level, and ignores the social and political determinants of health and right to health that have been supported by decades of international work and commitments. UHC risks commodifying health care, which threatens the underlying principles of UHC of equity in access and of health care as a collective good.